2013
DOI: 10.5603/ep.2013.0006
|View full text |Cite
|
Sign up to set email alerts
|

First report on the validity of a continuous Metabolic Syndrome score as an indicator for Metabolic Syndrome in a national sample of paediatric population — the CASPIAN-III study

Abstract: Pierwsze doniesienie na temat wyniku oceny trafności ciągłego wskaźnika zespołu metabolicznego jako wskaźnika obecności zespołu metabolicznego przeprowadzonej w ogólnokrajowej próbie reprezentatywnej populacji pediatrycznej -badanie CASPIAN-III AbstractIntroduction: The aim of this study was to assess the validity of a continuous Metabolic Syndrome score (cMetS) in a nationally representative sample of Iranian children and to identify sex and age-specific optimal cut-off points of cMetS that are associated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 43 publications
0
29
0
1
Order By: Relevance
“…Otro país es Turquía, donde se ha reportado una prevalencia del SM de 2.3% en adolescentes de 10-19 años 39 o de 2.5-4.4% en niños de primaria y secundaria dependiendo del método de diagnóstico utilizado40 . De igual manera, Irán tiene una prevalencia del SM de 5.3% en niños de 6 a 11 años 41 , de 6.5% en adolescentes entre 15 a 18 años 42 , y de 4.4% en adolescentes de 10-18 años43 . Mientras que las prevalencias del SM altas han sido reportadas en países como Italia (niños y adolescentes de 6 a 14 años con 13.0%)44 .…”
unclassified
“…Otro país es Turquía, donde se ha reportado una prevalencia del SM de 2.3% en adolescentes de 10-19 años 39 o de 2.5-4.4% en niños de primaria y secundaria dependiendo del método de diagnóstico utilizado40 . De igual manera, Irán tiene una prevalencia del SM de 5.3% en niños de 6 a 11 años 41 , de 6.5% en adolescentes entre 15 a 18 años 42 , y de 4.4% en adolescentes de 10-18 años43 . Mientras que las prevalencias del SM altas han sido reportadas en países como Italia (niños y adolescentes de 6 a 14 años con 13.0%)44 .…”
unclassified
“…Of these 24 papers, 22 report about the development of one or more risk model or score [24][25][26][27][28][29][30][31][32][33][34][35]37,38,[40][41][42][43][44][45][46][47], and 2 studies report about the development and external validation of one or more risk model or scores on an external population [36,39].Overall, the 24 studies reported 40 models, out of which 24 models were selected for full data extraction. The rest (16 models) were not selected, either because they were judged to be minimally different from the reported ones or they were not the preferred models by the authors or they were significantly deficient in details or statistical reporting.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the age of the sample, more risk scores were reported in adults than in children or adolescent. Of the 24 included models, 15 risk models were focused on adult subjects [24,25,29,[31][32][33][34][35][36][37][38][41][42][43][44]47], while 8 targets children and adolescents [26][27][28]30,39,40,45,46]. Table 4.0 shows the details of the components of the included 24 risk models or scores as well as their statistical properties-which includes (where available) their "sensitivity, specificity, discrimination, calibration, positive and negative predictive values, AUROC".…”
Section: Resultsmentioning
confidence: 99%
“…We have previously published the methodology of the cMetS score calculation in detail [ 29 ]. In brief, the cMetS score was computed by standardizing the residuals (z-scores) of WC, MAP, HDL-C, TG, and FBG by regressing them according to age and sex to account for age and gender-related differences.…”
Section: Methodsmentioning
confidence: 99%